2007
DOI: 10.1111/j.1439-0329.2007.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic patterns of Armillariaostoyae in the western United States

Abstract: Nuclear ribosomal DNA regions (i.e. large subunit, internal transcribed spacer, 5.8S and intergenic spacer) were sequenced using a direct-polymerase chain reaction method from Armillaria ostoyae genets collected from the western USA. Many of the A. ostoyae genets contained heterogeneity among rDNA repeats, indicating intragenomic variation and likely intraspecific hybridization. Intragenomic variation was verified by visually editing base-sequence offsets in regions with insertions/deletions, and using sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 87 publications
2
26
0
Order By: Relevance
“…Although isolate M70 has been previously identified as A. gallica by pairing tests (Morrison et al 1985) and nuclear DNA content (Kim et al 2000), AFLP data also showed this isolate as genetically distinct from the other two A. gallica isolates (ST22 and ST23) (Kim et al 2006). These data, as well as other DNA sequence data (Kim et al 2006;Hanna et al 2007), suggest that A. gallica is a diverse species that comprises multiple, genetically distinct groups which may include cryptic species (Hawksworth 2010). Confirmation of cryptic species within A. gallica will require sequence analysis of more genetic regions within multiple isolates from diverse sources.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Although isolate M70 has been previously identified as A. gallica by pairing tests (Morrison et al 1985) and nuclear DNA content (Kim et al 2000), AFLP data also showed this isolate as genetically distinct from the other two A. gallica isolates (ST22 and ST23) (Kim et al 2006). These data, as well as other DNA sequence data (Kim et al 2006;Hanna et al 2007), suggest that A. gallica is a diverse species that comprises multiple, genetically distinct groups which may include cryptic species (Hawksworth 2010). Confirmation of cryptic species within A. gallica will require sequence analysis of more genetic regions within multiple isolates from diverse sources.…”
mentioning
confidence: 70%
“…Armillaria isolates used in this study More detailed information on the Armillaria isolates used in this study is available inKim et al 2006 NABS, North American biological species a JF313133 (ST11A), JF313134 (ST11B); for isolate ST11, the method ofHanna et al (2007) was used to decipher and edit a ''frame-shift'' caused by length variation between two gene copies, from which two separate sequences (ST11A and ST11B) were generated…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…focussing on the ITS, IGS1, and LSU regions of rDNA, Hanna et al (2007) reported that heterogeneous rDNA products were common in all of these regions. rDNA heterozygosity has also been reported in diploid European A. gallica isolates (Pérez-Sierra et al 1999), A. sinapina (White et al 1998), and Armillaria nabsnona .…”
Section: S Gene and Igs2 Region Sequencesmentioning
confidence: 99%
“…A. ostoyae represents a circumboreal parasite on conifers, while A. gemina prefers hardwood hosts and is geographically restricted to the northeastern US, Ontario, and Québec (Burdsall and Volk 1993). Although geographic subgroups of A. ostoyae have been identified (Hanna et al 2007), the low metabolic diversity was also found with our European reference strain (A. ostoyae FVA 600), whereas high metabolic diversity was typical of A. mellea. In the past, various studies utilized the structural variation of a natural product class within a fungal genus or a species to establish chemotypes of the respective organisms.…”
Section: Discussionmentioning
confidence: 52%